The impact of gamification on customer engagement and customer loyalty from users of shopee in Samarinda - Ariesta Heksarini; Aulia Safira Putri (INOVASI, 2022)
The increase in internet users in Indonesia has resulted in a rapid increase in e-commerce transactions in recent years. As a result, e-commerce companies compete with one another to increase customer engagement and loyalty. The gamification strategy is one of the approaches taken. This study aims to determine the impact of gamification on customer engagement and loyalty among Shopee users in Samarinda. The results show that Shopee Indonesia's gamification strategy has a significant and positive effect on customer engagement and loyalty.